Lake sediment characteristics from Feresjön, 2020-11-15 - Asa Research Station (Swedish University of Agricultural Sciences, 2025)
A comprehensive sediment survey carried out at the lakes of SITES Water to assess the main sediment characteristics (water content, organic carbon (C) and nitrogen (N) content and grain size distribution)
Asa Research Station (2025). Lake sediment characteristics from Feresjön, 2020-11-15 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/6lzyDMtyn5P6e2Y3ntIGa0mk
Keywords: Asa Research Station; Nitrogen; Organic Carbon; Sediments; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap